Fuzzy-based group decision-making approach utilizing a 2-tuple linguistic q-rung orthopair set for the selection of optimal watershed system model - Li, Jie; Saleh, Hind Y.; Salih, Areen A.; Rasheed, M. Waheed; Bilal, Muhammad; Shabbir, Nimra (Frontiers in Environmental Science, 2025)
Watershed system models are tools used to study and simulate the behavior of watersheds, which are areas of land where all the water drains to a common outlet, typically a river, lake, or ocean. These models are essential for understanding and managing water resources, predicting flood events, and assessing the impact of land use and climate changes on the environment. Moreover, these advanced models should also help in making better decisions about the watersheds. This paper presents an integrated novel approach for decision-making in the selection of a watershed system model called decision-making trial and evaluation laboratory (DEMATEL)-multi-objective optimization based on the ratio analysis (MOORA) framework. The proposed method employs the 2-tuple linguistic q-rung orthopair fuzzy set (2TLq-ROFS) and enables the integration of new knowledge into models through dynamic data-sharing mechanisms. The weights of attributes are determined by the application of the 2TLq-ROF-DEMATEL technique, while the 2TLq-ROF-MOORA approach is employed to establish the ranking of the alternatives. The weighted power Muirhead mean (WPMM) aggregation operator is subsequently expanded to incorporate the 2TLq-ROF information for aggregating data. Finally, in order to assess the feasibility of the given methodology, an illustration is employed to choose the most suitable watershed system model. Moreover, we establish the soundness and feasibility of our methodology through a comprehensive comparison with several existing methodologies. Finally, findings of the study are reviewed, and potential directions for future research are discussed.